Imaginative parallels. Re-reading the tropes of marriage and voluntary enclosure in Dorothea of Montau’s Vitae - Sikorska, Liliana (Studia Anglica Posnaniensia, 2025)
Medieval women, escaping the restrictions of marriage, frequently opted for an inner life dedicated to God. Rendered through the trope of the spiritual union to Christ, the mystical marriage underscored the medieval discrepancy between the mundane and the ideal. This divergence reverberates in Johann von Marienwerder’s hagiographic narrative of the life of an anchoress, Dorothea of Montau.[1] Married at an early age to an abusive older man, Dorothea found solace in secretly dedicating herself to the divine while following the rules of the Church and living in utter submission to her husband. Dorothea suffered as a battered wife, but, once widowed, excelled as an immured recluse. Relinquishing physical freedom, Dorothea gained spiritual emancipation. In Canon Johann’s Vitae, her earthly matrimony, even though a necessary ordeal for the future saint, is presented through the metaphors of imprisonment, and the anchoress’s cell, however claustrophobic, through the imagery of her liberating spiritual union with the divine. Such a representation, which is in accord with Lakoff & Johnson’s (2003: 5) straightforward definition of the essence of metaphor denoting “understanding and experiencing one kind of thing in terms of another”, will be the subject matter of the present paper. Warranting the imaginative parallels, what follows is an analysis of the earthly and unworldly matrimonies in Dorothea of Montau’s life in the historical context of the late fourteenth-century Prussia.